Experimental results on sand transport under waves in large-scale wave flume - Chung, Dang Huu (Vietnam Journal of Mechanics, 2000)
The paper presents some results of a study based on the experiment carried out in Delta Flume of Delft Hydraulics. The analysis of time-series of sand concentration and velocity are implemented for regular and irregular waves with different conditions on wave and grain size. From measured concentrations and velocities the suspended transport components are calculated and some interesting information is obtained. At the same time some formulae for calculations of suspended sediment transport have been proposed and verified. A general evaluation on the total sediment transport rate over the water depth has been given on the basis of incorporating measurement, extrapolation and bed load prediction.